Edson, Sherman County - Hansen, Maura (Kansas State University, The Chapman Center for Rural Studies, 2016)
The following is a brief history of Edson, Washington Township, Sherman County, Kansas. Edson is a community that has managed to maintain its small population for over 100 years, and has relied heavily on the railroad along the way. This study uses personal interviews, on site photography, Sherman County history books, and a number of other local resources.
Maura Hansen, “Edson, Sherman County,” Chapman Center Research Collections, accessed October 21, 2020, https://ccrsresearchcollections.omeka.net/items/show/179.
Keywords: Albert and Laura Harris; Homesteaders; Ogallala aquifer; Rock Island Line; Sherman County; Washington Township